An overview of the sixth international conference on the comparative biology of monocotyledons - monocots VI - Natal, Brazil, 2018 - Versieux, Leonardo M.; Calvente, Alice; Carvalho, Fernanda Antunes; Fonseca, Carlos Roberto; Lichston, Juliana Espada; Voigt, Eduardo; Fontes, Anderson Lopes; Roque, Alan; Williams, Joseph Hill; de Oliveira, Reyjane Patrícia; Viana, Pedro Lage; Mercier, Helenice; et al. (FapUNIFESP (SciELO), 2021)
In this paper we present an overview of the abstracts, scientific and social programs, field trips, and achievements in terms of participant number, represented countries, sponsorships, and themes treated during the Sixth International Conference on the Comparative Biology of Monocotyledons that took place in Natal, Brazil, October 7th -12th 2018. Some comments received by the organizers and a few suggestions for organizers of the next meeting, in Costa Rica, are also provided. The conference’s complete abstract book was published and provide additional information.
Keywords: Araceae; Botany; Bromeliaceae; Monocots; Poaceae